Radon Concentrations in Canned Liquid Juice - A. A. Abojassim (PPIKSN-BATAN, 2021)
This study was performed at University of Kufa, Iraq, using canned liquid juice samples found in Iraqi markets due to the absence of environmental contamination from radionuclides emitting 222Rn concentrations using RAD-7 detectors. The annual effective dose (AED) of 222Rn was estimated for children and adults from the ingestion of canned liquid juice samples. The estimated concentrations of 222Rn in unit (mBq/L) ranged from 35.4 to 249.1, with an average of 77.880.24 ± 15.42. It also shows that the AED values for children and adults in (nSv/y) ranged from 19.11 to 134.48 with an average of 43.31 ± 8.32 and from 22.67 to 159.55 with an average of 51.39 ± 9.88, respectively. All estimated results of 222Rn concentrations for juice samples were lower than the natural limits provided by the WHO and the European Union Commission to the public (0.5 and 1 Bq/L, respectively). Therefore, there are no health hazards from drinking juice sold in Iraq markets.